Regulating the Tyrell Corporation: the Emergence of Novel Beings. (July 2021) - Lawrence, David R; Morley, Sarah
Abstract: Emerging biotechnologies and advances in computer science promise the arrival of novel beings possessed of some degree of moral status, even potentially sentient or sapient life. Such a manifestation will constitute an epochal change, and perhaps threaten Homo sapiens' status as the only being generally considered worthy of personhood and its contingent protections; as well as being the root of any number of social and legal issues. The law as it stands is not likely to be capable of managing or adapting to this challenge. This paper highlights the likely societal ramifications of novel beings and the gaps in the legislation which is likely to be relied upon to respond to these. In so doing, the authors make a case for the development of new regulatory structures to manage the moral issues surrounding this new technological upheaval.